Senior International Officers: Essential Roles and Responsibilities - Ogundimu, Adesola (Journal of International Students, 2020)
As internationalization efforts in higher education have grown in scale and impact over the last few decades, sound institutional leadership, policies, and practices that are rooted in a clear appreciation of the purpose of internationalization have become even more crucial for advancing socially responsible standards of success (Brandenburg et al., 2019). Areas such as developing a strategic plan for internationalization and fostering institutional partnerships globally are key responsibilities that require effective leadership and are critical for higher education institutions (Kwai, 2017). Senior International Officers: Essential Roles and Responsibilities is one of the few existing guides on the emerging role of the Senior International Officer (SIO), an administrative position often tasked with the oversight of all matters relating to internationalization.